2014
DOI: 10.1089/lrb.2013.0020
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Self-Measurement Protocol Development and Daily Variation Between Healthy Volunteers and Breast Cancer Survivors with Lymphedema

Abstract: Background: A significant percentage of breast cancer survivors are at risk for lymphedema for which lifelong self-care is required. Previous studies suggest that less than 50% of breast cancer survivors with lymphedema (BCS-LE) perform prescribed self-care tasks and that even wearing a compression sleeve, the most commonly reported self-care activity, is done irregularly. Reasons for poor self-care adherence include perceived lack of results from self-care (no available arm volume data) and perceived inabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…BIS was administered to measure the impedance of each arm, which scales with the extracellular fluid content of the arm. 12 The L-Dex ratio is reported as a standardized measure of the ratio of the impedance of extracellular water in the affected limb compared to the unaffected limb. 13 Qualitative and quantitative MRI measures of tissue structure MRI measurements were performed at 3 Tesla (Philips Medical Systems, Best, The Netherlands) using dual-channel body coil radiofrequency transmission and a 16-channel torso coil for reception.…”
Section: Non-mri Measurementsmentioning
confidence: 99%
“…BIS was administered to measure the impedance of each arm, which scales with the extracellular fluid content of the arm. 12 The L-Dex ratio is reported as a standardized measure of the ratio of the impedance of extracellular water in the affected limb compared to the unaffected limb. 13 Qualitative and quantitative MRI measures of tissue structure MRI measurements were performed at 3 Tesla (Philips Medical Systems, Best, The Netherlands) using dual-channel body coil radiofrequency transmission and a 16-channel torso coil for reception.…”
Section: Non-mri Measurementsmentioning
confidence: 99%
“…Newman and colleagues demonstrated that bioimpedance spectroscopy has sufficient sensitivity to assess not only extracellular fluid volume, but also lean mass and fat mass between affected and unaffected extremities of Stage II unilateral breast cancer-related lymphedema patients, which could provide additional diagnostically-relevant metrics to monitor the progression of later-stage lymphedema (104). Most recently, and arguably most excitingly, Ridner et al recently developed and reported the first self-measurement protocol for bioimpedance testing, which may pave the way for a home-use diagnostic in the future (105). …”
Section: Interstitial Changesmentioning
confidence: 99%
“…19 After completion of baseline assessments, participants were randomized (1:1 allocation) into either a BIS self-measurement intervention or standard care control group using a computer-generated, permuted block randomization scheme developed prior to implementation of the study. (Fig.…”
Section: Designmentioning
confidence: 99%
“…19 The Food and Drug Administration (FDA) has approved a BIS device to measure changes in extracellular fluid associated with lymphedema. 20 This device is small, portable, and gives numerical output (L-Dex readings) informing the patient if extracellular fluid is above normal ranges.…”
mentioning
confidence: 99%